Women Fishers’ Access to Economic Resources from the Perspectives of Gender Equality and Legal Justice - Sitepu, Ied Veda; Panjaitan, Hulman; Saragi, Paltiada (Journal of Law, Politic and Humanities, 2025)
Women Fishers’ Access to Economic Resources from the Perspectives of Gender Equality and Legal Justice discusses systemic marginalization despite women fishers’ significant contribution to fisheries through post-harvest work, small-scale industries, and even active fishing. This exclusion limits their access to economic resources, and consequently, health services, small-scale fishermen’s loan or even state protection. The objectives of the paper is to examine how patriarchal cultural norms and information asymmetries marginalize women from being recognized as fishers, restrict their access, and how exclusionary legal definitions of “fisher” systematically limit women’s economic participation.The study  uses normative legal research method (normative juridical) with statutory analysis and a sociological legal research method (sociological juridical) to seek and identify the relationship between abstract legal concepts and reality by reviewing legal products that are not gender-responsive and cultural practices that reinforce inequality and discriminatory regulations, patriarchal traditions, and poor access to information collectively hinder women’s economic participation. Achieving gender equality in coastal areas requires reforms in legal recognition, education, and policy implementation to ensure women’s rights as fishers are upheld, thereby advancing social justice and inclusive maritime development.